Development of an innovative technology for accelerated cooking of no yeast bread using ion-ozonized water - Iztayev, Auyelbek; Alimardanova, Mariam; Iztayev, Bauyrzhan; Yerzhanova, Mira; Tungyshbayeva, Ulbala; Izteliyeva, Raushan; Tursunbaeva, Sholpan (Eastern-European Journal of Enterprise Technologies, 2021)
Natural baking starter made from common ingredients such as flour, water and sugar is considered healthy. Any starter obtained by spontaneous fermentation is always a symbiosis of lactic acid bacteria and yeast. Lactic acid bacteria and yeast get along well together and in the course of their life enrich bread with the most valuable compounds, including short-chain organic acids, dietary fiber, essential amino acids, vitamins, etc. On the basis of the obtained research results, a recipe and technological modes for preparing dough for no yeast bakery products from wheat flour of the first grade with the use of ion-ozonized water, whey and natural starter have been developed. The dough was prepared in a safe way under pressure in a kneading-beating ion-ozone cavitation unit. The recipe components (raw materials) of the dough were loaded into the kneading body of the unit, then the dough was replaced for 5 minutes at a kneading body rotation frequency of 5 s-1 in different rotation modes and times. Then the ion-ozone treatment was carried out using an excess pressure of 0.40 MPa (cavitation) and the dough was knocked down. The nutritional value, safety and shelf life of the developed no yeast bakery products with the addition of whey, starter and ion-ozonized water have been determined. It was found that in terms of organoleptic and physicochemical indicators, bread samples prepared from first grade wheat flour and ion-ozonized water without yeast and using whey are almost 2 times inferior to the quality of the control sample. As a result, it was found that churning for 3–5 minutes at a kneading body rotation frequency of 4–5 s-1 will be the optimal mode for obtaining a no yeast dough made from first grade flour on starter with the addition of whey and ion-ozonized water